An improved double chamber triaxial volume change measurement system for unsaturated soils - Wu, Tingyu; Xia, Chaobo; Chen, Hui; Xu, Xiaocong; Pan, Daoming; Chen, Jun (Frontiers in Built Environment, 2025)
It is crucial to accurately measure the volume change of specimens in triaxial tests on unsaturated soils. A new type of inner chamber structure has been designed for measuring volume changes, which can accurately measure the volume change of unsaturated soils during monotonic loading tests. Compared to conventional double chamber triaxial systems, the new inner chamber structure has higher precision and compatibility, and the inner chamber can be assembled under air-free water. The inner chamber assembled underwater avoids the problem that the air bubbles being trapped in the inner chamber, significantly reducing the impact of residual air in the system. A solid specimen made of stainless steel was used to calibrate the newly designed inner chamber. Under the net confining pressure (the difference between cell pressure and the initial cell pressure) of 400 kPa, the volume change error of system is only 0.037% of specimen volume, the measurement error is very small. The contact surface between the loading ram and the top cover is coated with Teflon material and smeared with Vaseline to reduce friction, and the friction force measured by high-precision force gauge is 4.14 N. Drained shear test was conducted on an undisturbed saturated soft clay specimen, where the volume change in the saturated soil specimen during drainage was used to verify the accuracy and precision of the inner chamber volume measurement method. The volume change error measured by the system during consolidation and shearing are 0.102% and 0.067% of specimen volume, respectively. The results indicate that the newly designed inner chamber structure is feasible for volume change measurement and has high precision.